Efficiency of Labiateae plants essential oils against adults of cotton whitefly (Bemisia tabaci) - ZANDI-SOHANI, NOOSHIN (The Indian Journal of Agricultural Sciences, 2026)
The toxicity of essential oil vapours distilled from thyme (Zataria multiflora Boiss), rosemary (Rosmarinus officinalis L.), Savory (Satureja hortensis L.), Penny royal (Mentha pulegium L.) and spearmint (Mentha viridis L.) were tested against adults of cotton whitefly (Bemisia tabaci Gennadius). Insects were exposed at time 3, 6, 9, 12 and 24 hr and the amounts of the essential oils were 2, 4, 6 and 8 Î¼l in each desiccator with 4l capacity, corresponding to 0.5, 1, 1.5 and 2 Î¼l/ l air. The essential oil vapours of all five species caused the highest mortality in 2 Î¼l/l air doses and 24hr of exposure time in this species. In general, higher mortality was observed as the doses of essential oils and exposure period increased. The results showed that the essential oil of five aromatic plants have the potential to be used for management of B. tabaci in greenhouse conditions. M. pulegium and M. viridis essential oils caused the highest mortality of B. tabaci adults (78.75 and 78.19%), respectively. The mean mortality caused by essential oils of Z. multiflora, R. officinalis and S. hortensis were 69.02, 54.3 and 53.47% respectively.